Modelling and Analysis of Novel Topology for Multilevel Inverter With Reduce Number of Switches - Kumar, Rohit; S.L, Shimi; Kaura, Shivendra (International Journal of Engineering and Technology, 2018)
The demand of quality power is increasing continuously. The problem of global warming and rate of decrease of non-renewable energy sources are increasing day by day. Hence renewable energy sources such as fuel cell, solar, Magneto hydro Dynamic (MHD), geothermal are the best alternatives to solve the problem of environmental issue and increasing demand of energy.Â The output of these resources is dc, therefore to connect these resources to the grid, multilevel inverter is the key device. But the output of multilevel inverter has power quality issues such as harmonic generation and notching due to conversion of dc to ac and high number of switch. Hence, this paper deals with harmonic elimination using Genetic Algorithm based Selective Harmonic Elimination (GA-SHE) techniques for asymmetric and symmetric topology of MLI. In the present study, comparative study among the 5-level, 7-level, 9-level, 11-level and 15-level multilevel inverters with reduced number of switches topologies has been discussed. A novel topology of 15-level inverter which consists least number of switches has been designed for a desired voltage level. Also, the comparison of Total harmonic distortion developed in the output voltage generated by different topology at different levels with the proposed 15-level inverter topology are discussed.Â